PANDANGAN TENTANG PRAKTIK BEDAH PLASTIK DALAM ARTIKEL OPINI DI SURAT KABAR KOREA TAHUN 2010–2019 - Adnyana, Putu Pramania; Muta'ali, Abdul; Suganda, Sonya Puspasari (UI Scholars Hub, 2024)
This research aims to reveal Korean’s perspectives on plastic surgery practices through a corpus-based text analysis of Korean online newspapers. The research used quantitative and qualitative methods to observe keywords, significant collocates, and semantic preference. The data used were 106 opinion articles about plastic surgery in Chosun Ilbo and Donga Ilbo (2010–2019). Keyword analysis shows that the most frequently used keywords are seonghyeong (189 times) and seonghyeongsusul (116 times). Analysis of significant collocates and semantic preferences revealed that plastic surgery was frequently discussed in relation to body parts, people (collocate yeoseong (women), junggukin (Chinese), hwanja (patient), gwangganggek (tourist)), country (collocate jungguk (China), hangguk (Korea)), intensity (gwadohan (excessive)), and effect (phihae (loss)), and others. Plastic surgery clinics are frequently addressed in terms of location (collocate Gangnam, Seoul), intensity (collocate daehyong (big scale)), and others. Based on the findings of this study, plastic surgery is primarily performed on local women and international patients, particularly Chinese tourists. Plastic surgery is also perceived as having a negative impact, being overdone, and causing numerous difficulties. Plastic surgery performed on foreign patients is considered as beneficial to Korean economic progress, but it should not be performed on Koreans.